Challenges in tendon–bone healing: emphasizing inflammatory modulation mechanisms and treatment - Jiang, Fan; Zhao, Haibo; Zhang, Po; Bi, Yanchi; Zhang, Haoyun; Sun, Shenjie; Yao, Yizhi; Zhu, Xuesai; Yang, Fenghua; Liu, Yang; Xu, Sicong; Yu, Tengbo; et al. (Frontiers in Endocrinology, 2024)
Tendons are fibrous connective tissues that transmit force from muscles to bones. Despite their ability to withstand various loads, tendons are susceptible to significant damage. The healing process of tendons and ligaments connected to bone surfaces after injury presents a clinical challenge due to the intricate structure, composition, cellular populations, and mechanics of the interface. Inflammation plays a pivotal role in tendon healing, creating an inflammatory microenvironment through cytokines and immune cells that aid in debris clearance, tendon cell proliferation, and collagen fiber formation. However, uncontrolled inflammation can lead to tissue damage, and adhesions, and impede proper tendon healing, culminating in scar tissue formation. Therefore, precise regulation of inflammation is crucial. This review offers insights into the impact of inflammation on tendon-bone healing and its underlying mechanisms. Understanding the inflammatory microenvironment, cellular interactions, and extracellular matrix dynamics is essential for promoting optimal healing of tendon-bone injuries. The roles of fibroblasts, inflammatory cytokines, chemokines, and growth factors in promoting healing, inhibiting scar formation, and facilitating tissue regeneration are discussed, highlighting the necessity of balancing the suppression of detrimental inflammatory responses with the promotion of beneficial aspects to enhance tendon healing outcomes. Additionally, the review explores the significant implications and translational potential of targeted inflammatory modulation therapies in refining strategies for tendon-bone healing treatments.